1997
DOI: 10.1021/tx970137b
|View full text |Cite
|
Sign up to set email alerts
|

Amination of Tyrosine in Liver Cytosol Protein of Male F344 Rats Treated with 2-Nitropropane, 2-Nitrobutane, 3-Nitropentane, or Acetoxime

Abstract: Previously, the secondary nitroalkane 2-nitropropane, a strong hepatocarcinogen in rats, had been shown to induce the formation of 8-aminoguanine in both DNA and RNA of rat liver through a sulfotransferase-mediated pathway. This pathway was postulated to convert the carcinogen into an aminating species [Sodum, R. S., et al. (1994) Chem. Res. Toxicol. 7, 344-351]. To submit this postulate to further test, we examined liver proteins of rats treated with 2-nitropropane, other carcinogenic secondary nitroalkanes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…We have previously demonstrated by in vivo and in vitro studies that aryl sulfotransferase is essential for the formation of all three RNA and DNA nucleoside modifications, a finding recently corroborated by others (7,8). We have also proposed the formation of an unsubstituted nitrenium ion, NH 2 + (7), as an ultimate reactive species in the activation pathway of 2-nitropropane (Scheme 1) capable of aminating proteins and nucleic acids (6,7,9). The observed reactions of hydroxylamine-O-sulfonic acid, a proposed metabolic intermediate (6) in Scheme 1, with guanosine to generate both 8-amino-and 8-oxoguanines (Scheme 2), and tyrosine to give 3-aminotyrosine, support the proposed pathway (6,9).…”
Section: Introductionsupporting
confidence: 52%
“…We have previously demonstrated by in vivo and in vitro studies that aryl sulfotransferase is essential for the formation of all three RNA and DNA nucleoside modifications, a finding recently corroborated by others (7,8). We have also proposed the formation of an unsubstituted nitrenium ion, NH 2 + (7), as an ultimate reactive species in the activation pathway of 2-nitropropane (Scheme 1) capable of aminating proteins and nucleic acids (6,7,9). The observed reactions of hydroxylamine-O-sulfonic acid, a proposed metabolic intermediate (6) in Scheme 1, with guanosine to generate both 8-amino-and 8-oxoguanines (Scheme 2), and tyrosine to give 3-aminotyrosine, support the proposed pathway (6,9).…”
Section: Introductionsupporting
confidence: 52%
“…The stepwise nature of the hydrodynamic voltammetry curve of the reduced species in Fig. 1B which is markedly different from that shown by 3-aminotyrosine (34), suggests that the reduction of 3-nitrotyrosine may proceed through several intermediates, probably including the nitroso and the hydroxylamine forms. Voltages higher than ϩ0.6 V were not used at the downstream electrode to minimize the background current.…”
Section: Figmentioning
confidence: 67%
“…HPLC coupled with electrochemical detection is reported to be the most sensitive method [21] but has the disadvantage that nitrotyrosine is reduced to 3-aminotyrosine to ensure satisfactory sensitivity [22]. Moreover, 3-aminotyrosine is reported to be produced in i o (0.1-1.5 mol of 3-aminotyrosine\10 kmol of tyrosine) [23] via tyrosine amination, so endogenous 3-aminotyrosine might cause interference with the sample of interest. HPLC with electrochemical detection has been used to measure 3-nitrotyrosine in a range of disease states [17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 3-aminotyrosine is reported to be produced in i o (0.1-1.5 mol of 3-aminotyrosine\10 kmol of tyrosine) [23] via tyrosine amination, so endogenous 3-aminotyrosine might cause interference with the sample of interest. HPLC with electrochemical detection has been used to measure 3-nitrotyrosine in a range of disease states [17][18][19][20][21][22][23][24]. In one study the concentration of nitrotyrosine in human plasma proteins was reported as 2.3 µmol\mol of tyrosine [18] (0.2 ng\mg) and in another as being below the limit of detection to 4.2 ng\mg [2].…”
Section: Discussionmentioning
confidence: 99%